Diameter of the Bony Lacrimal Canal: Normal Values and Values Related to Nasolacrimal Duct Obstruction: Assessment with CT - Janssen, Alfred G.; Mansour, Khaled; Bos, Johanna J.; Castelijns, Jonas A. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Epiphora, or tearing due to primary acquired nasolacrimal duct obstruction (PANDO), is increasingly being treated with balloon dilatation. The cause of PANDO is unknown, but a small diameter of the bony nasolacrimal canal might be one of the etiologic factors. The purpose of this study was to determine the normal distribution of diameters of the bony canal and to ascertain whether there is an association between the diameter of the bony canal and primary nasolacrimal duct obstruction.METHODS: Using axial CT, we measured the minimum diameter of the bony nasolacrimal canal in a control group of 50 men and 50 women and in 19 patients with PANDO.RESULTS: The mean minimum diameter in the control group was 3.5 mm, which was smaller than expected on the basis of published data. The difference between the mean minimum diameter in men (3.70 mm) and that in women (3.35 mm) was significant. The mean minimum diameter in the patient group was 3.0 mm, which was significantly smaller than that in the control group. There was, however, considerable overlap.CONCLUSION: A small diameter of the bony canal appears to be one of the etiologic factors in PANDO.